Ecosystems: Broadening the locus of value creation - Rahul Kapoor (Journal of Organization Design, 2018)
The objective of this article is to introduce readers to the emerging research stream on business ecosystems, explicating the novelty and the usefulness of ecosystem-based theorizing, and hoping to pave the way for an influential but cumulative body of knowledge. The key tenets within an ecosystem-based perspective are outlined and used to contrast this emerging perspective from other established perspectives of value chains, supply chains, alliances, and networks. The article concludes by discussing the research approaches that can be employed to study ecosystems and the implications for organization design.
Keywords: 650; Betriebliches Umfeld; Betriebliche Wertschöpfung; Strategisches Management; Organisationsforschung